Peran guru bimbingan dan konseling dalam membina kemandirian belajar siswa - Sutaji, Sutaji; Renata, Dian; Satrianta, Hengki (Orien: Cakrawala Ilmiah Mahasiswa, 2024)
this study aims to determine the role of guidance and counseling teachers in fostering student learning independence. This study uses a descriptive qualitative method. The results of the study are that the role of guidance and counseling teachers for student learning independence at SMK Kesehatan Gapura Merah Putih Jagakarsa has been running well. BK teachers have also provided information or fostered learning independence related to the future journey of students who need education. The strategy was completely successful with the note that some students must be given extra guidance and counseling so that they have personal awareness to increase their learning independence by providing understanding, direction, and directions for independence so that they are active in studying to achieve their desired goals.